The EU HELCATS Project, WP7, Task 7.1: Combining Observations of Interplanetary Scintillation (IPS) and Heliospheric Visible-Light Imaging of CMEs and SIRs - Bisi, M. M.; Barnes, D.; Eastwood, J.; Krupař, V. (Vratislav); Magdalenic Zhukov, J.; Fallows, R.; Harrison, R.; Davies, J. (2017)
The Heliospheric Cataloguing, Analysis and Techniques Service (HELCATS) project is one of the European Union's Seventh Framework Programme (EU FP7) projects. The project ends in April 2017. It is primarily targeted to the cataloguing of transient and background structures observed in the heliosphere by the visible-light Heliospheric Imagers (HIs) on board the Solar-TEerestrial RElations Observatory (STEREO) twin spacecraft mission, including identification of their source regions and in-situ signatures. The current version of the HELCATS manually-generated Coronal Mass Ejection (CME) Catalogue contains more than 1,000 CMEs observed between 2007 and 2017, and the current HELCATS Stream Interaction Region (SIR) Catalogue contains signatures of nearly 200 co-rotating density structures in the ecliptic plane. The HELCATS project includes an assessment of the complementary nature of ground-based radio observations of interplanetary scintillation (IPS), which is yielding catalogues of IPS features (from EISCAT/MERLIN/ESR and/or LOFAR data, where available) that are being compared to the STEREO HI catalogues (under WP7 Task7.1). Here, we discuss the final status of this Task of the HELCATS project and we provide insights that have been gleaned from preliminary analyses of this joint cataloguing exercise. Such insights relate, in particular, to the space-weather exploitation of these two complementary observational techniques. For example, there are cases where a CME is imaged by the STEREO HI instruments but then not detected using IPS, and vice versa.